NPS–EQA PART II: Four years’ experience in external quality assessment program in Italy for classical and new psychoactive substances analysis in hair - Rotolo, Maria Concetta; Graziano, Silvia; Varì, Maria Rosaria; Minutillo, Adele; Di Giorgi, Alessandro; Aquilina, Valeria; Pichini, Simona; Marchei, Emilia (Journal of pharmaceutical and biomedical analysis, 2024)
In 2019, the Italian National Institute of Health established an external quality assessment (EQA) program to evaluate the performance of laboratories of collaborative centres participating in the National Early Warning System in hair testing for classical and new psychoactive substances (NPS). The results obtained in the four rounds (2019–2023) and the evolution in hair testing performance for classic drugs of abuse and new psychoactive substances are presented. A total of 11 hair specimens, including 3 blank samples, were prepared by adding different classes of classical and NPS at known concentrations to pre-screened drug-free hair. False negative and false positive results were calculated for the qualitative data evaluation. The quantitative evaluation included the imprecision (as % coefficient of variation, CV%) and the accuracy (as % error, ERR%) of the results with respect to a mean value obtained by reference laboratories and Z-score values were assessed. Over the years, an improvement in false negative results (from 52.4% in the first year to 34.3% in the last one) and false positive results (from 55.0% in the first year to 30.8.% in the last one) was observed. In the first round, the mean ERR% ranged from 6.2% to 112.8% due to NPS determination. However, in the subsequent three rounds, the mean ERR% ranged from 10.4% to 22.4%, The mean CV% in the four rounds was approximately 41.5% (ranging from 44.3% to 53.3%). Between 12.0% and 56.6% of the reported results in all rounds should be considered satisfactory. EQA programs help laboratories to identify and correct problems within their processes by highlighting errors and variations. This ensures that the results produced are accurate and reproducible. •The identification of new psychoactive drugs is a constant challenge for laboratories.•Hair analysis detects past and chronic use of both classic drugs of abuse and NPS.•External quality assessment, a quality tool for evaluating laboratory performance.•EQA programmes are crucial for NPS hair analysis in clinical and forensic settings.